2023
DOI: 10.3389/fpsyg.2023.1117369
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life and depressive symptoms of patients with chronic diseases and the general population before and during the COVID-19 pandemic in Korea

Abstract: ObjectiveThe unprecedented coronavirus disease 2019 (COVID-19) outbreak has resulted in a global crisis that negatively impacted physical well-being and mental health. Our goal was to investigate the impact of the COVID-19 pandemic on health-related quality of life (HRQoL) and depressive symptoms in patients with chronic diseases and the general population in Korea.MethodsData from 8341 patients with chronic diseases and 12,395 general population aged ≥20 years who participated in the Korea National Health and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 59 publications
0
1
1
Order By: Relevance
“…The lone statistical interaction effect showed a larger tradeoff between loss of close social connectedness and a measure of the emotional and psychological toll (PII-N) specifically related to the pandemic (Table 3; Figure 2). While prior research has shown that people living at higher risk from their chronic illness were more likely to experience mental health problems [23,24,26,28], this study shows that the loss of contacts they felt close to was associated with even greater feelings of worthlessness, disconnection, worry, or lacking meaning in life (PII-N items) related to COVID-19 than the respondents without chronic illness. Notably, this finding was limited to COVID-19-specific psychosocial distress, while those with chronic illnesses tended to mirror the healthier respondents regarding their general psychological distress response.…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…The lone statistical interaction effect showed a larger tradeoff between loss of close social connectedness and a measure of the emotional and psychological toll (PII-N) specifically related to the pandemic (Table 3; Figure 2). While prior research has shown that people living at higher risk from their chronic illness were more likely to experience mental health problems [23,24,26,28], this study shows that the loss of contacts they felt close to was associated with even greater feelings of worthlessness, disconnection, worry, or lacking meaning in life (PII-N items) related to COVID-19 than the respondents without chronic illness. Notably, this finding was limited to COVID-19-specific psychosocial distress, while those with chronic illnesses tended to mirror the healthier respondents regarding their general psychological distress response.…”
Section: Discussioncontrasting
confidence: 76%
“…During the early stages of the pandemic, there was limited investigation into the incipient and unfolding mental health impacts of COVID-19 lockdown policies, particularly on individuals with chronic diseases [ 23 ]; however, research on the effects of quarantine during the Middle East Respiratory Syndrome (MERS) outbreak found that these individuals had elevated clinical anxiety and depression levels [ 24 ] and increased odds for clinically significant anxiety 4–6 months post quarantine [ 25 ]. Since that first year of the pandemic response, multiple studies have shown that individuals with chronic diseases may be an especially vulnerable population for mental health sequelae [ 26 , 27 , 28 ]. However, more research on the effects of the COVID-19 pandemic on their mental health is needed [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among community-based adults in China, depression and HRQoL were inversely associated [ 80 ]. On all dimensions, HRQoL was found to be significantly lower in patients with chronic diseases compared with the general population in Korea [ 81 ]. Depression was found to affect HRQoL negatively in individuals with HIV [ 82 ], breast cancer [ 83 ] and diabetes mellitus [ 84 ].…”
Section: Discussionmentioning
confidence: 99%
“…HQoL is a subset of the broader QoL concept, focusing particularly on health dimensions, whereas QoL, as defined here, encompasses a wider range of life domains, including social, emotional, and physical aspects (Whoqol, 1998). The dimensions of QoL usually encompass physical health, psychological state, level of independence, social relationships, and environmental factors (Park and Park, 2023;Puce et al, 2023).…”
Section: Theoretical Frameworkmentioning
confidence: 99%